ANALISIS PENGARUH KOMPENSASI FINANSIAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN (Studi Pada Karyawan PT. Newmont Nusa Tenggara) - S Syafruddin; Laela Novadia; Vivin Fitryani (Samalewa: Jurnal Riset & Kajian Manajemen, 2022)
This study aims to determine the effect of financial compensation on employee productivity at PT. Newmont Nusa Tenggara. The population in this study are all employees of PT. Newmont Nusa Tenggara. Researchers set a sample quota of 100 respondents who were taken by simple random sampling or simple random samples. This number is considered to represent the results of the study because it meets the requirements as a large sample. The variables used in this study are Direct Financial Compensation (X1) and Indirect Financial Compensation (X2) as independent variables, and Employee Productivity (Y) as the dependent variable. Data were obtained directly from respondents through questionnaires, namely data collection by distributing a list of questions to respondents who were used as research samples. Data analysis technique using multiple linear regression analysis. The results showed that the variables of direct financial compensation and indirect financial compensation had a positive and significant effect on the work productivity of employees at PT. Newmont Nusa Tenggara, both partially and simultaneously, this has been proven through the t test and f test. The degree of influence of direct financial compensation and indirect financial compensation on the work productivity of employees of PT. Newmont Nusa Tenggara is 79.3%, while the remaining 20.7% is influenced by other variables outside this research model.